(untitled) (Harmoni, 2014)
This article argues that the social dynamics of conflict in Papua do not always consist of conflict. The case of Fakfak, West Papua demonstrates that peace and harmony also exists. This study utilizes the qualitative descriptive analysis method to study data gathered from observations made during fieldwork, interviews, and primary and secondary documents. The article argues two main points. First, religion and culture have an important role in building social norms of harmony that influence the social behavior of the individuals in social arenas such as politics and economics. Second, the institutionalization of values and norms are supported by both the government and civil society when they share the same vision for promoting peace and harmony. However, this study also acknowledges that factors such as separatism and religious radicalism, if not handled well, can break the harmonious social integration in Fakfak.